Pemanfaatan Aplikasi Canva sebagai Strategi Penguatan Citra UMKM Rezki Berkah Sehati - Mariyanti, Eka; Astri, Renita; Vitri, Gusni; Azman, Heru Aulia; Lusia, Siska; Srihasnita, Rita; Indrayeni, Indrayeni; Abdilla, Mohammad; Nasrah, Rasidah (Jurnal Pengabdian Masyarakat Dharma Andalas, 2025)
This community service activity aims to enhance the graphic design and digital marketing skills of members of UMKM Rezki Berkah Sehati in West Sumatra. Through Canva application training, participants are expected to create more attractive and effective promotional materials and strengthen their products' visual identity. In addition to the training, the Pusat Studi Pengembangan Nagari (PSPN) of Universitas Dharma Andalas also facilitated the UMKM to showcase their products through a booth at a mini UMKM bazaar. The results of this training showed a significant improvement in graphic design understanding, as well as the use of social media for product promotion. Despite some challenges related to the limited time for intensive mentoring, this activity successfully enhanced the competitiveness of UMKM and opened broader market opportunities. Moving forward, the development of training materials and the expansion of collaboration with various stakeholders will further strengthen the entrepreneurial ecosystem in West Sumatra.